Theoretical Approach for the Design of a New Wideband Ku-band Printed Antenna - Harrabi, A.; Razban, T.; Mahe, Y.; Osman, L.; Gharsallah, A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A design of a broadband Ku-band low-cost printed circuit board technology (PCB) antenna is presented in this paper. An approach was developed to enhance the bandwidth of a simple printed patch antenna. The proposed method is, step by step, detailed to discuss the evolution of the antenna geometry and depicts the contribution of the imported changes on the properties achieved each time. A 22% relative bandwidth in Ku-band was obtained for a footprint of 0.4?0×0.6?0 (?0 is the wavelength in the free space). A good agreement between the simulation and the measurement results of the wideband patch was observed, which proves the interest of this approach.